(untitled) (Praxis Educativa, 2018)
We present partial results of the research “The construction of didactic knowledge of content in experienced and beginners teachers of the UNNE. Multi-case study”, whose objective is the understanding of the processes of construction of the professional knowledge of university teachers, specifically related to the didactic- echnological knowledge of the content (TPACK). We propose the analysis of eachers’ representations on the use of ICTs in teaching proposals and in student earning experiences, central aspects to locate the technological dimension in different levels of curricular integration in the aulic projects. We report 4 case studies consisting of arratives of experienced teachers of single-paradigmatic and multiparadigmatic disciplines of two Academic Units of the UNNE. Based on the analysis and interpretation of the different modes of integration of digital technologies, we note the emergence of indications that account for the complex relationships between didactic, technological and disciplinary knowledge.